2015
DOI: 10.1016/j.pepi.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the mechanical properties imaged by seismic tomography during an EGS creation at The Geysers (California) and geomechanical modeling

Abstract: Using coupled thermal-hydro-mechanical (THM) modeling, we evaluated new seismic tomography results associated with stimulation injection at an EGS demonstration project at the northwest Geysers geothermal steam field, California. We studied high resolution seismic tomography images built from data recorded during three time periods: a period of two months prior to injection and during two consecutive one month periods after injection started in October 2011. Our analysis shows that seismic velocity decreases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Moreover, as shown in Fig. 19, Jeanne et al (2015a) found a general trend of decreasing V P and V S with calculated steam pressure. V S decreases with pressure in areas where pressure is sufficiently high to cause shear failure, which in the field would correspond to areas where shear reactivation of pre-existing fractures and high microseismic density occur.…”
Section: Interpretation Of Seismic Tomography Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…Moreover, as shown in Fig. 19, Jeanne et al (2015a) found a general trend of decreasing V P and V S with calculated steam pressure. V S decreases with pressure in areas where pressure is sufficiently high to cause shear failure, which in the field would correspond to areas where shear reactivation of pre-existing fractures and high microseismic density occur.…”
Section: Interpretation Of Seismic Tomography Resultssupporting
confidence: 55%
“…Coupled THM modeling in Jeanne et al (2015a) showed that seismic V P and V S velocities decrease in areas with the most intense microseismicity; this is also correlated with the spatial distribution of calculated steam-pressure changes. This correlation can be observed by comparing Vp and Vs distribution in Fig.…”
Section: Interpretation Of Seismic Tomography Resultsmentioning
confidence: 74%
See 3 more Smart Citations